Unsuccessful Invitro-fertilization and an ectopic pregnancy - Yee Kyaing, Yee; Abigail Rembui, Jerip
Introduction: As changes in lifestyles and living environments, infertility is increasing globally and affecting 8-12% of couples worldwide. At the same time, there has been an increase demand for assisted reproductive technologies (ART). Case Description: A 36 -year-old gravida 4 Parity 0+3 lady was referred to hospital. Her previous 3 consecutive pregnancies received by intrauterine inseminations ended in first trimester miscarriages. Current pregnancy was received by invitro fertilization (IVF) treatment. Nine days after treatment, her urine pregnancy test was positive. Ultrasound revealed that endometrial thickness 20 millimetres, both ovaries were normal and right adnexal mass measuring 1.38 x 1.5 centimeters. There was no free fluid in the abdomen. Her serial serum β hCG rising was suboptimal and it was diagnosed as an ectopic pregnancy. As she was asymptomatic and her vital signs were stable, injection methotrexate was given. Follow-ups after treatment, serum β hCG returned to normal. Discussion: Ectopic pregnancy is a well-known complication following invitro fertilization (IVF). The incidence of ectopic pregnancy is between 2.1% to 8.6% after IVF which is higher than natural conceptions. Increased incidence of ectopic pregnancy following IVF could be due to the effects of the treatment or the pre-existing disorders. Transvaginal ultrasound scan together with serum β hCG monitoring between 4 to 6 weeks of pregnancy makes early diagnosis and it prevents maternal morbidity and mortality.